Analisis Hubungan Antar Organisasi dalam Pengembangan Investasi di Kawasan Perdagangan dan Pelabuhan Bebas Batam - Ady Muzwardi; Achmad Nurmandi (Universitas Muhammadiyah Yogyakarta, 2014)
Investment is one source of state revenue. Until now the investment management in Indonesia can not be managedoptimally, because one of them by a system of investment management organization that is still weak. This study aimedto analyze the relationship between the organization (network governance) in organizing system in the developmentof investment in the Free Trade Zone and Free Port of Batam. The method used is the analysis of network coordina-tion with the study of the 5 aspects including governance structures, karaketristik service, operational interactionpar tner characteristics and network characteristics on a 3-level organization of provincial and district/city. The analy-sis finds that the coordination between the provincial and district organizations / cities still not optimal. coordinationhorizontally and vertically has not established optimally.